Injury in aged animals robustly activates quiescent olfactory neural stem cells - Brann, Jessica H.; Ellis, Deandrea P.; Ku, Benson S.; Spinazzi, Eleonora F.; Firestein, Stuart (Frontiers in Neuroscience, 2015)
While the capacity of the olfactory epithelium (OE) to generate sensory neurons continues into middle age in mice, it is presumed that this regenerative potential is present throughout all developmental stages. However, little experimental evidence exists to support the idea that this regenerative capacity remains in late adulthood, and questions about the functionality of neurons born at these late stages remain unanswered. Here, we extend our previous work in the VNO to investigate basal rates of proliferation in the OE, as well as after olfactory bulbectomy (OBX), a commonly used surgical lesion. In addition, we show that the neural stem cell retains its capacity to generate mature olfactory sensory neurons in aged animals. Finally, we demonstrate that regardless of age, a stem cell in the OE, the horizontal basal cell (HBC), exhibits a morphological switch from a flattened, quiescent phenotype to a pyramidal, proliferative phenotype following chemical lesion in aged animals. These findings provide new insights into determining whether an HBC is active or quiescent based on a structural feature as opposed to a biochemical one. More importantly, it suggests that neural stem cells in aged mice are responsive to the same signals triggering proliferation as those observed in young mice.